KAJIAN STRUKTUR DAN NILAI KARAKTER DALAM ARSIP TEKS UPA-UPA: PEMANFAATAN SEBAGAI E-MODUL INTERAKTIF PEMBELAJARAN SASTRA (SYAIR) BERMUATAN KEARIFAN LOKAL DI SEKOLAH MENENGAH PERTAMA (SMP) - Nuralamsyah Nasution, - (2023)
As time progresses, many local traditions and cultural wisdom in various regions are gradually fading away. The same holds true for the upa-upa tradition in Mandailing Natal, which, if not preserved, faces the risk of further endangerment. Upa-upa is an ancient form of poetry conveyed by poets during the pinnacle of wedding ceremonies. It possesses a unique structure compared to conventional poetry and reflects the values of the Mandailing Natal community. This research aims to describe: 1) the text structure of upa-upa archives in Mandailing, 2) the character values within traditional upa-upa oral literature, and 3) the design of interactive teaching materials in the form of an e-module for oral literature education at the junior high school level, incorporating local wisdom. The research adopts a qualitative approach with descriptive analysis as the method. Based on the findings, it is revealed that: 1) The structure of upa-upa poetry is defined by the number of lines and syllables, representing a type of oral literature in the form of traditional regional poetry. 2) The structure of upa-upa poetry is open to textual variations. 3) The language used in upa-upa poetry does not necessarily adhere to archaic language. 4) Religious and cultural values are dominant, emphasizing the significance of religion, prayer, and obedience to God's commandments. These values reflect the strong identity and character of the Mandailing Natal community in preserving their traditions, culture, and religious life. 5) The findings and discussions of this research are suitable for serving as a source for designing an interactive e-module to convey these values to junior high school students. This research contributes to the preservation of oral literature, specifically the upa-upa tradition.